Hubungan Kebiasaan Merokok Dengan Kejadian Tb Paru Di Wilayah Kerja Puskesmas Sidomulyo - Murfikin, Fakhmi -; Dewi, Ari Pristiana; Woferst, Rismadefis - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the relationship of smoking and the incidence of pulmonary tuberculosis in PuskesmasSidomulyo. Methods used in this study was a retrospective study. The selection of samples using incidental sampling technique with 33 respondents. Measuring instrument used was a questionnaire with 8 questions. The analysis used univariate and bivariate analysis.Results of studies using pieces of chi-square statistical test showed no association between smoking duration variables, the type and number of cigarettes cigarettes in suction with pulmonary TB incidence in PuskesmasSidomulyo (p value = 0.149), (p value = 0.186), (p value = 1.000).Based on the results of these studies are expected to be input in the sale of the health hazards of other diseases caused by smoking, although this study did not result in getting the relationship between smoking and pulmonary tuberculosis, but the promotion of the health hazards of smoking can be improved so that it can avoid other diseases caused by smoking. Keyword : Incidence ofpulmonary tuberculosis, Smoking habits